Extension of Darbo’s fixed point theorem via shifting distance functions and its application - Nashine, Hemant Kumar; Das, Anupam (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we discuss solvability of infinite system of fractional integral equations (FIE) of mixed type. To achieve this goal, we first use shifting distance function to establish a new generalization of Darbo’s fixed point theorem, and then apply it to the FIEs to establish the existence of solution on tempered sequence space. Finally, we verify our results by considering a suitable example.